1974
DOI: 10.1007/bf01976426
|View full text |Cite
|
Sign up to set email alerts
|

The function of an MBC-releasing deposit of benomyl and thiophanates in plant roots and soil

Abstract: A comparative study has been made on the effects of short-term treatment versus long-term treatment with benomyl and three thiophanates with regard to distribution of fungitoxicant (MBC, or EBC) within plants and their protection against fungal diseases. In both treatments, plants were exposed to the fungicides for two days and then transplanted to garden soil; long-term treated plants received an additional supply of fungicide as a daily drench for one week.Results of short-term treatment of cucumber seedling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1975
1975
1984
1984

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The differences observed between the effects of the two fungicides might be due to a different ability of MBC and thiophanate-methyl (or an intermediate conversion product; Fuchs et al, 1972) to function as an MBC-releasing deposit in plant roots and soil (Fuchs et al, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…The differences observed between the effects of the two fungicides might be due to a different ability of MBC and thiophanate-methyl (or an intermediate conversion product; Fuchs et al, 1972) to function as an MBC-releasing deposit in plant roots and soil (Fuchs et al, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…In the first tests, The effectiveness of triforine and imazalil against the benomyl-resistant strain can best be explained by their different mode of action. Benomyl and its breakdown product MBC~ the compound mainly responsible for the fungitoxicity of this fungicide (Clemons and Sisler, 1969;Sims et al, 1969;Fuchs et al, 1972Fuchs et al, , 1974Petsikos-Panayotarou, 1972), have been found to inhibit mitosis in different fungi (Davidse, 1973;Hammerschlag and Sisler, 1973;Richmond and Phillips, 1975). iOn the contrary, triforine has been found to inhibit sterol biosynthesis (Sherald et al, 1973;Sherald and Sisler, 1975).…”
Section: Discussionmentioning
confidence: 96%
“…The long-term effects of benzimidazole fungicides deposited in the soil on the control of plant diseases have been discussed in detail by Fuchs, Fernandes & de Vries (1974). The long-term effects of benzimidazole fungicides deposited in the soil on the control of plant diseases have been discussed in detail by Fuchs, Fernandes & de Vries (1974).…”
Section: Discussionmentioning
confidence: 99%